The determination of spins and lifetimes of excited nuclear states by resonance fluorescence techniques - Buitendag, J. J.(Jan Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1970.